Chipping behaviour of all-ceramic crowns with zirconia framework and CAD/CAM manufactured veneer - Schmitter, Marc; Müller, Denise; Rues, Stefan (Journal of dentistry, 2012)
Objectives: The aim of this in vitro study was to assess the ultimate load to failure of zirconia based crowns veneered with CAD/CAM manufactured ceramic. Methods: 32 identical, anatoform zirconia (Sirona inCoris ZI, mono L F1) frameworks (thickness 0.6mm) were constructed (Sirona inLab 3.80). Afterwards, 16 crowns were completed using a CAD/CAM manufactured lithium disilicate ceramic veneer (IPS e.max CAD, Ivoclar Vivadent). The remaining 16 frames were veneered using conventional manual layering technique. For the CAD/CAM manufactured veneers, the connection between framework and veneer was accomplished via a glass fusion ceramics. Before fracture tests, half of the specimens underwent thermocycling and chewing simulation (1.2 million chewing cycles, force magnitude Fmax=108N). To further investigate the new technique, finite element computations were carried out on the basis of the original geometry. Results: Nearly all (87.5%) conventionally veneered crowns failed already during chewing simulation, whereas crowns with CAD/CAM manufactured veneers were non-sensitive to artificial ageing. Crowns veneered with lithium disilicate ceramic displayed ultimate loads to failure of about 1600N. Conclusion: The CAD/CAM production of veneers for restorations with zirconia framework is a promising way to reduce failures originating from material fatigue.